Effect of Ionospheric Perturbation on GPS Observation over Low Latitude Region, Bhopal - Chatterjee, S.; Purohit, P. K. (Journal of Scientific Research, 2012)
Increased knowledge on the ionospheric structure is of important interest for precise positioning, since the ionosphere has an impact on global positioning system (GPS) L-band radio waves by its free electrons. Especially during perturbed geomagnetic conditions when the ionosphere differs from its undisturbed state, quasi real time data assimilation would be useful. On the other hand, these perturbations of the GPS signals are taken as scientific information to investigate ionospheric scenarios. In this paper we describe the occurrence of GPS phase fluctuations during January to December 2005 events on the basis of Bhopal GPS observations. This study concerns the analysis of strong phase fluctuations which were associated with geomagnetic storms. The intensive total electron content (TEC) fluctuations observed along GPS satellite passes, demonstrate a strong horizontal gradient of TEC and difficulties with the carrier phase ambiguity in relative GPS positioning. In turn, the phase fluctuations can cause cycle slips. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i3.10146 J. Sci. Res. 4 (3), 577-587 (2012)